Hydrochar: A Promising Step Towards Achieving a Circular Economy and Sustainable Development Goals - Padhye, Lokesh P.; Bandala, Erick R.; Wijesiri, Buddhi; Goonetilleke, Ashantha; Bolan, Nanthi (Frontiers in Chemical Engineering, 2022)
The United Nations 17 Sustainable Development Goals (SDGs) are a universal call to action to end poverty, protect the environment, and improve the lives and prospects of everyone on this planet. However, progress on SDGs is currently lagging behind its 2030 target. The availability of water of adequate quality and quantity is considered as one of the most significant challenges in reaching that target. The concept of the ‘Circular Economy’ has been termed as a potential solution to fasten the rate of progress in achieving SDGs. One of the promising engineering solutions with applications in water treatment and promoting the concept of the circular economy is hydrochar. Compared to biochar, hydrochar research is still in its infancy in terms of optimization of production processes, custom design for specific applications, and knowledge of its water treatment potential. In this context, this paper critically reviews the role of hydrochar in contributing to achieving the SDGs and promoting a circular economy through water quality treatment and incorporating a waste-to-value approach. Additionally, key knowledge gaps in the production and utilization of engineered hydrochar are identified, and possible strategies are suggested to further enhance its water remediation potential and circular economy in the context of better natural resource management using hydrochar. Research on converting different waste biomass to valuable hydrochar based products need further development and optimization of parameters to fulfil its potential. Critical knowledge gaps also exist in the area of utilizing hydrochar for large-scale drinking water treatment to address SDG-6.